Systematic Literature Review: Impact of the Teams Games Tournament Model on Conceptual Understanding - Nurjanah, Tri; Prihaswati, Martyana; Purnomo, Eko Andy (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study was conducted to determine the effect of the Teams Games Tournament model on conceptual understanding. The purpose of this study was to determine the effect of the Teams Games Tournament learning model on conceptual understanding. This study uses the systematic literature review (SLR) method, employing a review procedure focused on selected reporting items for systematic review. The method involves reviewing various journal articles on Google Scholar from 2019 to 2025, using the keywords “Teams Games Tournament learning model” and “conceptual understanding ability.” A total of 985 articles were identified, with 26 main articles selected for use. The review process consisted of three stages: Planning, Conducting, and Reporting. The results of this study indicate that the Teams Games Tournament learning model has an impact on conceptual understanding ability. These findings suggest that the Teams Games Tournament learning model is effective in enhancing students' conceptual understanding ability. It is hoped that future researchers will not limit their focus to Google Scholar alone.